Spectral Dye Absorbance Investigation of Complex Ions Zinc-Alkali Chloride in Aqueous Methanol-Pyridine Systems - N. Modi, Ashvin; Desai, C.M. (Asian Journal of Chemistry, 2010)
Absorbance spectral investigation using dye indicator has been investigatedto study changes in complex ions formation with changes in aqueousphase.